Effects of high-grain or high-roughage transition diets on finishing performance of cattle previously fed high-concentrate growing diets - Montgomery, Sean P.; Sindt, J.J.; Farran, T.B.; LaBrune, H.J.; Hunter, R.D.; Higgins, James J.; Nutsch, T.A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred twenty-eight crossbred beef steers previously fed high-concentrate growing diets had ad libitum access to one of two transition diets prior to initiation of the finishing phase. Transition diets consisted of 58% steam-flaked corn and 30% alfalfa hay or of 23% steamflaked corn and 65% alfalfa hay (DM basis). Average daily gains, dry matter intakes, and feed efficiencies during the transition phase were greater for steers fed the high-grain diet than for steers fed the high-roughage diet (P<.01). This resulted in heavier carcass weights at the end of the subsequent finishing phase for steers fed the high-grain transition diet (P<.05). Average daily gains and feed efficiencies in the finishing phase were not affected by the type of diet fed during the transition phase (P>.20).
Keywords: Beef; Transition Diet; Grain; Roughage; Finishing cattle